ممارسات القيادة الإبداعية وتأثيرها في تحقيق التميز المؤسسي في المؤسسات الجزائرية - ثورية رضواني; مسعود نملي; فاطمة الزهرة ديك (university of eloued جامعة الوادي, 2024)
"هدفت هذه الدراسة إلى التعرف على ممارسات القيادة الإبداعية وأبعادها (حساسية المشكلات، المثابرة، المبادرة، المرونة) وتأثيرها في تحقيق التميز المؤسسي في المؤسسات الجزائرية، دراسة حالة المؤسسة التجارية موبيليس بالوادي. ولتحقيق أهداف البحث تم استخدام المنهج الوصفي التحليلي كما تم الاعتماد على استمارة استبيان المكونة من جزئين خصص الأول للبيانات الشخصية للمبحوثين، أما الثاني تم تقسيمه إلى محورين حيث تضمن المحور الأول متغير القيادة الإبداعية موزع على أربعة أبعاد وكل بعد مكون من أربع عبارات، كما تضمن المحور الثاني متغير التميز المؤسسي وكما احتوى على عشرة عبارات. ولدراسة الحالة استخدمنا أسلوب المسح الشامل وتم توزيع (30) استمارة استبيان على العاملين في المؤسسة التجارية موبيليس بالوادي بجميع فروعها وتم استرجاع الاستمارات الصالحة للتحليل (30) أي بنسبة 100% وتم اعتماد على البرنامج الإحصائي للعلوم الإنسانية (spss) للحصول على النسب والتكرار والأوساط الحسابية وكذلك الارتباط والتأثير بين متغيرات البحث، ومن أهم النتائج التي توصلت إليها الدراسة الحالية وجود علاقة ارتباط موجبة بين ممارسات القيادة الإبداعية والتميز المؤسسي، كما تبين أن هناك أثر بين ممارسات القيادة في الإبداعية في تحقيق التميز المؤسسي. وأوصت الدراسة إلى الحرص على تهيئة بيئة العمل المناسبة للموظفين من أجل تحسين الخدمة " "This study aimed to identify creative leadership practices and their dimensions (sensitivity to problems, perseverance, initiative, flexibility) and their impact on achieving institutional excellence in Algerian institutions, a case study of the Mobilis commercial enterprise in El Oued. To achieve the research objectives, the descriptive analytical method was used, and a two-part questionnaire was relied upon. The first was devoted to the personal data of the respondents, while the second was divided into two axes, where the first axis included the creative leadership variable distributed over four dimensions, and each dimension consisted of four statements. The axis also included The second variable, institutional excellence, contained ten statements. To study the case, we used a comprehensive survey method, and (30) questionnaire forms were distributed to employees of the Mobilis commercial establishment in the valley in all its branches. (30) questionnaires suitable for analysis were retrieved, meaning 100%. We relied on the Statistical Program for the Human Sciences (SPSS) to obtain proportions, frequencies, and arithmetic means. As well as the connection and influence between the research variables, one of the most important findings of the current study is that there is a positive correlation between creative leadership practices and institutional excellence, and it has also been shown that there is an effect between leadership practices in creativity in achieving institutional excellence. The study recommended that care be taken to create an appropriate work environment for employees in order to improve service. "
Keywords: قيادة، قيادة إبداعية، تميز مؤسسي، المؤسسة التجارية موبيليس leadership; creative leadership; institutional excellence; Mobilis commercial enterprise